A review of recent merger and acquisitions in mobile telecommunications service industry: Substantial issues and implications for policy makers - Chalita Srinuan; Pratompong Srinuan (International Telecommunications Society (ITS), 2023)
Mobile telecommunications service industry has oligopolistic market structure. Four or three mobile network operators (MNOs) seem to be a magic number for telecom regulators as their competition safeguard. The merger and acquisition (M&A) process of MNOs has been a debate for several decades, both within industry and in academia. There are two forms of mergers which include mergers giving rise to market dominance (anti-merger) and mergers that provide for integration bringing efficiency and innovation (pro-merger). Therefore, this paper aims to explore the patterns, impacts, and specific measures regulatory agencies apply to mobile network providers who are doing through a merger process. From an extensive review of the articles published from 2012 2022, this paper reveals that most MNOs choose to use their stock as the primary acquisition tool. Also, most mergers resulted in a drop in the number of service providers from four to three, with all regulatory bodies ruling in favor of the merger except one (which was soon overturned by the court). Merger approval criteria by regulators have been wide-ranging. However, there has been much focus on the promotion of MVNOs (mobile virtual network operators) and assuring they have bandwidth access to the larger and well-established MNOs. Moreover, infrastructure sharing (such as towers) is another common merger condition as well as roaming agreements and spectrum returns to the government. As in the case of the United States mega-merger of Sprint and T-Mobile, assuring rural access to advanced, expensive, and high-speed technology like 5G becomes the operator's approval bargaining chip. This paper contributes to the international and regulatory discussions concerning the highly charged and complex subject of telecommunications M&A activity.
Keywords: 330; Business integration; Case studies; Merger and acquisitions; Mobile phones; wireless communications carriers